Effects of multistrain Bifidobacteria and Lactobacillus probiotics on HMO compositions after supplementation to pregnant women at threatening preterm delivery: design of the randomized clinical PROMO trial - A. Welp; E. Laser; K. Seeger; A. Haiß; K. Hanke; K. Faust; G. Stichtenoth; C. Fortmann-Grote; J. Pagel; J. Rupp; W. Göpel; M. Gembicki; et al. (SpringerOpen, 2024)
Abstract Background As an indigestible component of human breast milk, Human Milk Oligosaccharides (HMOs) play an important role as a substrate for the establishing microbiome of the newborn. They have further been shown to have beneficial effects on the immune system, lung and brain development. For preterm infants HMO composition of human breast milk may be of particular relevance since the establishment of a healthy microbiome is challenged by multiple disruptive factors associated with preterm birth, such as cesarean section, hospital environment and perinatal antibiotic exposure. In a previous study it has been proposed that maternal probiotic supplementation during late stages of pregnancy may change the HMO composition in human milk. However, there is currently no study on pregnancies which are threatened to preterm birth. Furthermore, HMO composition has not been investigated in association with clinically relevant outcomes of vulnerable infants including inflammation-mediated diseases such as sepsis, necrotizing enterocolitis (NEC) or chronic lung disease. Main body A randomized controlled intervention study (PROMO = probiotics for human milk oligosaccharides) has been designed to analyze changes in HMO composition of human breast milk after supplementation of probiotics (Lactobacillus acidophilus, Bifidobacterium lactis and Bifidobacterium infantis) in pregnancies at risk for preterm birth. The primary endpoint is HMO composition of 3-fucosyllactose and 3'-sialyllactose in expressed breast milk. We estimate that probiotic intervention will increase these two HMO levels by 50% according to the standardized mean difference between treatment and control groups. As secondary outcomes we will measure preterm infants' clinical outcomes (preterm birth, sepsis, weight gain growth, gastrointestinal complications) and effects on microbiome composition in the rectovaginal tract of mothers at delivery and in the gut of term and preterm infants by sequencing at high genomic resolution. Therefore, we will longitudinally collect bio samples in the first 4 weeks after birth as well as in follow-up investigations at 3 months, one year, and five years of age. Conclusions We estimate that probiotic intervention will increase these two HMO levels by 50% according to the standardized mean difference between treatment and control groups. The PROMO study will gain insight into the microbiome-HMO interaction at the fetomaternal interface and its consequences for duration of pregnancy and outcome of infants.